2022
DOI: 10.1037/xhp0000981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complexity and similarity of an interruption task on resilience toward interruptions in a procedural task with sequential constraints.

Abstract: The goal of the present study was to examine effects of complexity and similarity of an interruption task on postinterruption performance in an 8-step procedural task with sequential constraints. In Experiment 1, the primary task was interrupted between different steps with 1 of 4 versions of n-back task, which differed in complexity (simple, complex) and similarity in processing codes (verbal, spatial) to the primary task. After the interruption, participants (N = 44) had to resume the primary task as quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In line with previous studies which used procedural tasks as primary task (e.g., UNRAVEL task by Altmann et al, 2014 ; see also Radović & Manzey, 2022 ), we found that task interruptions prolong the processing time of the subtask performed immediately after the interruption, reflecting resumption costs (for reviews, see, e.g., Couffe & Michael, 2017 ; Hirsch et al, 2022 ). This indicates that the resumption of the primary task relies on time-consuming cognitive processes like proposed in the SAS model, the prospective memory view, and the memory for goals model.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies which used procedural tasks as primary task (e.g., UNRAVEL task by Altmann et al, 2014 ; see also Radović & Manzey, 2022 ), we found that task interruptions prolong the processing time of the subtask performed immediately after the interruption, reflecting resumption costs (for reviews, see, e.g., Couffe & Michael, 2017 ; Hirsch et al, 2022 ). This indicates that the resumption of the primary task relies on time-consuming cognitive processes like proposed in the SAS model, the prospective memory view, and the memory for goals model.…”
Section: Discussionsupporting
confidence: 90%
“…However, less common multitasking pairs were also observed, such as managing non-resident related work while preparing medications or transferring residents while documenting in the MAR. Cognitive experimental research shows that dissimilar stimuli increase response time and errors 40. Therefore, as a basis for development of clinical solutions, further study is needed to identify which multitasking pairs are interruptive within medication management workflows.…”
mentioning
confidence: 99%